Pematahan Dormansi Benih Merbau (Intsia bijuga (colebr) O. Kuntze) dengan Kombinasi Perlakuan Konsentrasi dan Lama Perendaman dalam Urin Sapi - Desy Khristiana Bana; Astin E. Mau; Norman P. L. B. Riwu Kaho; Pamona S. Sinaga (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
Merbau (Intsia bijuga (Colebr) O. Kuntze) is a tree species that naturally grows in various soil types, including moist, dry, and rocky soils, and is endemic to Indonesia. One of the main challenges in the generative propagation of Merbau is slow germination caused by its hard seed coat, due to the seed’s dormancy traits. Therefore, a pre-treatment is needed to break the dormancy, such as applying plant growth regulators (PGRs) through seed soaking. This study aimed to determine the effect of cow urine concentration and soaking duration on breaking seed dormancy in Merbau. A factorial Completely Randomized Design (CRD) was used with two factors: concentration (control/distilled water, 25%, 50%, 75%, and 100% cow urine) and soaking duration (24, 36, and 48 hours). The results showed that the single treatment of 75% concentration (A3) and 48-hour soaking duration (D3) were the most effective in breaking seed dormancy. However, D3 was not significantly different from D2 (36 hours) in terms of germination rate and germination value. The interaction between concentration and soaking duration had no significant effect on germination speed index, germination rate, or germination value of Merbau seeds.